The influence of the CIELAB parameters on the perception of color after the use of whitening toothpastes - Natália Nascimento Odilon; Rafaela Silva Oliveira; Max José Pimenta Lima; Elisângela de Jesus Campos (Universidade Estadual de Campinas, 2021)
Aim: To evaluate the influence of the parameters L* a* b* on the variation of the color of bovine tooth enamel submitted to artificial darkening, after simulated brushing, with whitening toothpastes containing blue covarine. Methods: To undertake this study in vitro, 60 specimens (SP) were divided into 6 groups (n=10): control group (CGwater) and 5 test groups (GT1-Colgate Total 12, GT2-Oral-B 3D White Perfection, GT3- Colgate Luminous Instant White, GT4-CloseUp White Diamond Attraction, GT5-Sorriso Xtreme White). The specimens were darkened with coffee and submitted to simulated brushing for 6, 12, and 24 months. The alteration in the color was evaluated using CIELAB parameters and the ΔL, Δa, Δb and ΔE were calculated. The data was analyzed through generalized linear models using the R program and considering a level of significance of 5%. Results: The parameters L*, a* and the ΔL, Δa obtained better results in the test group than in the control group. There were no statistical differences between CG and the test groups for the evaluation of the b* parameter. In the evaluation of the Δb, the GT3 differed statistically from the CG. In relation to the ΔE, all the group tests showed a variation in color statistically greater than that of the CG and the GT4 showed the greatest variation, not differing from the GT3 during the periods studied. Conclusion: The mechanical and optical whitening agents positively influenced the values L*a* and b*, as well as in its variations and in the ΔE. It is important to emphasize, however, that to analyze tooth whitening it is necessary to evaluate their parameters together.